2019
DOI: 10.1523/jneurosci.3498-17.2019
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Regulation of Neuronal Progranulin Reveals a Critical Role for the Autophagy-Lysosome Pathway

Abstract: Deficient progranulin levels cause dose-dependent neurological syndromes: haploinsufficiency leads to frontotemporal lobar degeneration (FTLD) and nullizygosity produces adult-onset neuronal ceroid lipofuscinosis. Mechanisms controlling progranulin levels are largely unknown. To better understand progranulin regulation, we performed a genome-wide RNAi screen using an ELISA-based platform to discover genes that regulate progranulin levels in neurons. We identified 830 genes that raise or lower progranulin level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 100 publications
1
47
1
Order By: Relevance
“…To analyze the GRN levels in iNs, we performed ELISA on the culture supernatant [29]. The ELISA revealed higher GRN levels in RedPenMC than AMC, but not statistically significant (fig.7A), which reiterates our CITE-seq finding (described above) that neuronal GRN levels between AMC and RedPenMC are not significantly different.…”
Section: Resultssupporting
confidence: 68%
“…To analyze the GRN levels in iNs, we performed ELISA on the culture supernatant [29]. The ELISA revealed higher GRN levels in RedPenMC than AMC, but not statistically significant (fig.7A), which reiterates our CITE-seq finding (described above) that neuronal GRN levels between AMC and RedPenMC are not significantly different.…”
Section: Resultssupporting
confidence: 68%
“…We selected two human PDAC cell lines, MiaPaCa2 and PaTuT cells, with relatively high PGRN expression levels (Figure S3a-c It was demonstrated that pancreatic cancer cells down-regulated surface MHCI by autophagy-mediated degradation (31). Coincidentally, PGRN was shown to regulate autophagy in various cell types (32,33). PGRN-deficient mice showed defective degradation of autophagosomes under starvation (34), which was mediated by lysosomal enzymes cathepsin D (35).…”
Section: Pgrn Suppression Leads To Surface Mhci Upregulation and Dysfmentioning
confidence: 99%
“…GRN is a gene that encodes progranulin (PGRN) (Holler et al, 2017). PGRN can regulate lysosome function, and PGRN deficiency in neurons increases autophagy and causes abnormally enlarged lysosomes (Elia et al, 2019).…”
Section: Amyotrophic Lateral Sclerosis (Als) and Frontotemporal Demenmentioning
confidence: 99%